DISTRIBUSI EKONOMI ISLAM DALAM UPAYA MENJAGA KESEJAHTERAAN PRESPEKTIF MAQASHID SYARIAH IBNU QAYYIM AL-JAUZIYAH - Sujarwo, Muhammad Rizky Rahmadani (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study discusses economic distribution in Islam as a vital instrument for achieving social welfare based on the Maqashid Syariah perspective of Ibn Qayyim al-Jauziyah. Using a qualitative-descriptive approach and library research method, the study finds that distribution instruments such as zakat, infaq, sadaqah, and waqf (ZISWAF) serve not only as religious obligations but also as social mechanisms to promote justice and reduce economic inequality. The five core principles of Maqashid Syariah—ḥifẓ ad-dīn, ḥifẓ an-nafs, ḥifẓ al-‘aql, ḥifẓ an-nasl, and ḥifẓ al-māl—are directly linked to these instruments. The research confirms that the implementation of Islamic economic distribution can create holistic and sustainable welfare.